2016
DOI: 10.1021/acs.est.6b03066
|View full text |Cite
|
Sign up to set email alerts
|

Designing Industrial Networks Using Ecological Food Web Metrics

Abstract: Biologically Inspired Design (biomimicry) and Industrial Ecology both look to natural systems to enhance the sustainability and performance of engineered products, systems and industries. Bioinspired design (BID) traditionally has focused on a unit operation and single product level. In contrast, this paper describes how principles of network organization derived from analysis of ecosystem properties can be applied to industrial system networks. Specifically, this paper examines the applicability of particular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 54 publications
(24 citation statements)
references
References 48 publications
0
24
0
Order By: Relevance
“…Other researchers are developing web-based semantic approaches where ontologies are used to model resources and "wastes" at participating companies before an algorithm then pairs participants [218,219]. Inspired by Industrial Ecology's overall endeavor to mimic natural systems, Layton et al have demonstrated the applicability of food web matrices for the creation of sustainable industry networks for the case of carpet recycling [220]. Similarly, Mathur et al quantify the environmental benefits of a hypothetical Eco-Industrial Park that uses EoL photovoltaic waste as feedstock [221].…”
Section: Industrial Symbiosismentioning
confidence: 99%
“…Other researchers are developing web-based semantic approaches where ontologies are used to model resources and "wastes" at participating companies before an algorithm then pairs participants [218,219]. Inspired by Industrial Ecology's overall endeavor to mimic natural systems, Layton et al have demonstrated the applicability of food web matrices for the creation of sustainable industry networks for the case of carpet recycling [220]. Similarly, Mathur et al quantify the environmental benefits of a hypothetical Eco-Industrial Park that uses EoL photovoltaic waste as feedstock [221].…”
Section: Industrial Symbiosismentioning
confidence: 99%
“…ENA metrics that quantify information about system structure and qualities such as flow cycling, synergism, mutualism , etc. are calculated from [ T ] [54] , [57] , [58] , [59] . The ENA metric of interest here is ecological robustness, also known as the ecological fitness function – as will be used in this paper to avoid confusion with engineering robustness.…”
Section: Ecological Network Analysis and The Ecological Fitness Functmentioning
confidence: 99%
“…The irksome bur inspired the now indispensable Velcro (Velcro BVBA, 2020). Ecosystems, which over time have developed into cyclical systems where “waste” and “resources” are one and the same (Jelinski, Graedel, Laudise, McCall, & Patel, 1992), have more recently inspired engineers and designers toward biologically preferred closed‐loop network configurations that are also desirable from a traditional perspective (Chatterjee & Layton, 2020; Dave & Layton, 2020; Layton, Bras, & Weissburg, 2016b; Layton, Reap, Bras, & Weissburg, 2012; Reap, 2009).…”
Section: Introductionmentioning
confidence: 99%